SHAPE ANALYSIS OF FINE AGGREGATES USED FOR CONCRETE - He, Huan; Courard, Luc; Pirard, Eric; Michel, Frederic (Image Analysis and Stereology, 2016)
Fine aggregate is one of the essential components in concrete and significantly influences the material properties. As parts of natures, physical characteristics of fine aggregate are highly relevant to its behaviors in concrete. The most of previous studies are mainly focused on the physical properties of coarse aggregate due to the equipment limitations. In this paper, two typical fine aggregates, i.e. river sand and crushed rock, are selected for shape characterization. The new developed digital image analysis systems are employed as the main approaches for the purpose. Some other technical methods, e.g. sieve test, laser diffraction method are also used for the comparable references. Shape characteristics of fine aggregates with different origins but in similar size ranges are revealed by this study. Compared with coarse aggregate, fine grains of different origins generally have similar shape differences. These differences are more significant in surface texture properties, which can be easily identified by an advanced shape parameter: bluntness. The new image analysis method is then approved to be efficient for the shape characterization of fine aggregate in concrete.